# Examples On Differentiation Set-1

Go back to  'LCD'

Example - 26

Evaluate the derivatives of the following functions by first principles:

(a) $$f\left( x \right) = \log \left( {\sin x} \right)$$           (b) $$f\left( x \right) = \sin \left( {\log x} \right)$$       (c) $$f\left( x \right) = \sqrt[3]{{\sin x}}$$        (d) $$f\left( x \right) = {e^{{x^2}}}$$

Solution: These functions are all compositions of multiple functions and can easily be differentiated using the Chain rule. However, our purpose here is to differentiate them using first principles. This exercise, instead of being considered futile, should be seen as an application of your algebraic manipulation skills.

(a) \begin{align}f'\left( x \right) = \mathop {\lim }\limits_{h \to 0} \frac{{\log \left( {\sin \left( {x + h} \right)} \right) - \log \left( {\sin x} \right)}}{h}\end{align}

\begin{align}& = \mathop {\lim }\limits_{h \to 0} \frac{{\log \left( {\frac{{\sin \left( {x + h} \right)}}{{\sin x}}} \right)}}{h}\\& = \mathop {\lim }\limits_{h \to 0} \frac{{\log \left( {\frac{{\sin x\cos h + \cos x\sin h}}{{\sin x}}} \right)}}{h}\\& = \mathop {\lim }\limits_{h \to 0} \frac{{\log \left( {\cos h + \cot x\sin h} \right)}}{h}\\& = \mathop {\lim }\limits_{h \to 0} \frac{{\log \left\{ {\cos h\left( {1 + \cot x\tan h} \right)} \right\}}}{h}\\ &= \mathop {\lim }\limits_{h \to 0} \frac{{\log \left( {\cos h} \right)}}{h} + \mathop {\lim }\limits_{h \to 0} \frac{{\log \left( {1 + \cot x\tan h} \right)}}{h}\end{align}

\begin{align}& = \mathop {\lim }\limits_{h \to 0} \frac{{\cos h - 1}}{h} + \cot x\\&= 0 + \cot x\\ &= \cot x\end{align}

(b) $$f'\left( x \right) = \mathop {\lim }\limits_{h \to 0} \frac{{\sin \left( {\log \left( {x + h} \right)} \right) - \sin \left( {\log x} \right)}}{h}$$

$$=2\underset{h\to 0}{\mathop{\lim }}\,\frac{\cos \left\{ \frac{\log \left( x+h \right)+\log \left( x \right)}{2} \right\}\sin \left\{ \frac{\log \left( x+h \right)-\log \left( x \right)}{2} \right\}}{h}$$

$$=2\cos \left( \log \left( x \right) \right)\underset{h\to 0}{\mathop{\lim }}\,\left\{ \frac{\sin \left\{ \frac{1}{2}\log \left( 1+\frac{h}{x} \right) \right\}}{h} \right\}$$

$$=2\cos \left( \log \left( x \right) \right)\underset{h\to 0}{\mathop{\lim }}\,\left[ \left\{ \frac{\sin \left\{ \frac{1}{2}\log \left( 1+\frac{h}{x} \right) \right\}}{\frac{1}{2}\log \left( 1+\frac{h}{x} \right)} \right\}\,\,\cdot \,\,\frac{\frac{1}{2}\log \left( 1+\frac{h}{x} \right)}{h} \right]$$

$$= 2\cos \left( {\log \left( x \right)} \right)\mathop {\lim }\limits_{h \to 0} \left\{ {\frac{1}{2}\frac{{\log \left( {1 + \frac{h}{x}} \right)}}{{x \cdot \frac{h}{x}}}} \right\}$$

$$= \frac{{\cos \left( {\log \left( x \right)} \right)}}{x}$$

(c) $$f'\left( x \right) = \mathop {\lim }\limits_{h \to 0} \frac{{\sqrt[3]{{\sin \left( {x + h} \right)}} - \sqrt[3]{{\sin x}}}}{h}$$

$$= \mathop {\lim }\limits_{h \to 0} \frac{{\sin \left( {x + h} \right) - \sin \left( x \right)}}{h} \cdot \frac{1}{{{{\left[ {\sin \left( {x + h} \right)} \right]}^{2/3}} + {{\left( {\sin x} \right)}^{2/3}} + {{\left[ {\sin x \cdot \sin \left( {x + h} \right)} \right]}^{1/3}}}}$$

{This step was accomplished by rationalization}

$$= \frac{{\cos x}}{{3 \cdot {{\left( {\sin x} \right)}^{2/3}}}}$$

(d) $$f'\left( x \right) = \mathop {\lim }\limits_{h \to 0} \frac{{{e^{{{(x + h)}^2}}} - {e^{{x^2}}}}}{h}$$

$$= \mathop {\lim }\limits_{h \to 0} \frac{{{e^{{x^2} + {h^2} + 2xh}} - {e^{{x^2}}}}}{h}$$

$$= {e^{{x^2}}}\mathop {\lim }\limits_{h \to 0} \frac{{{e^{{h^2} + 2xh}} - 1}}{h}$$

$$= {e^{{x^2}}} \cdot 2x$$

Example – 27

Evaluate the derivatives of the following functions using the techniques developed in section - 3:

\begin{align}&\text{(a)} \quad f\left( x \right) = \left( {{x^2} + 3x} \right){\sin ^{ - 1}}x \qquad \qquad \qquad \qquad \quad \text{(b)} \quad f\left( x \right) = \tan \left( {\frac{{x + 1}}{{x + 2}}} \right)\\&\text{(c)} \quad f\left( x \right) = {\cos ^{ - 1}}\left( {\sqrt {1 - {x^2}} } \right) + \frac{{{x^2} + 2x + 3}}{{x + 2}} \qquad \text{(d)} \quad f\left( x \right) = \sqrt {4 - {{\tan }^{ - 1}}{x^2}} \end{align}

Solution: (a) This function can be differentiated by the Product Rule (Rule - 3)

\begin{align}&\frac{{d\left( {f\left( x \right)} \right)}}{{dx}} = \left( {{x^2} + 3x} \right)\frac{{d\left( {{{\sin }^{ - 1}}x} \right)}}{{dx}} + {\sin ^{ - 1}}x\frac{{d\left( {{x^2} + 3x} \right)}}{{dx}}\\&\qquad\qquad{\rm{ }} = \frac{{\left( {{x^2} + 3x} \right)}}{{\sqrt {1 - {x^2}} }} + \left( {{{\sin }^{ - 1}}x} \right) \cdot \left( {2x + 3} \right)\end{align}

(b) This function will be differentiated by the Chain rule (Rule 5); the argument $$\left( {\frac{{x + 1}}{{x + 2}}} \right)$$ can be differentiated by the Quotient rule (Rule 4):

\begin{align}& \qquad \qquad \frac{{d\left( {f\left( x \right)} \right)}}{{dx}}\\ &= \frac{{d\left\{ {\tan \left( {\frac{{x + 1}}{{x + 2}}} \right)} \right\}}}{{d\left( {\frac{{x + 1}}{{x + 2}}} \right)}} \cdot \frac{{d\left( {\frac{{x + 1}}{{x + 2}}} \right)}}{{dx}}\\ &= {\sec ^2}\left( {\frac{{x + 1}}{{x + 2}}} \right) \cdot \frac{{\left( {x + 2} \right) \cdot \left( 1 \right) - \left( {x + 1} \right) \cdot \left( 1 \right)}}{{{{\left( {x + 2} \right)}^2}}}\\&\frac{1}{{{{\left( {x + 2} \right)}^2}}} \cdot {\sec ^2}\left( {\frac{{x + 1}}{{x + 2}}} \right) \end{align}

(c) Here, we will have to use a combination of these techniques as follows:

\begin{align}\frac{{d\left( {f\left( x \right)} \right)}}{{dx}} &= \left\{ {\frac{{ - 1}}{{1 - {{\left( {\sqrt {1 - {x^2}} } \right)}^2}}}} \right\} \cdot \frac{{ - x}}{{\sqrt {1 - {x^2}} }} + \frac{{\left( {x + 2} \right)\left( {2x + 2} \right) - \left( {{x^2} + 2x + 3} \right) \cdot \left( 1 \right)}}{{{{\left( {x + 2} \right)}^2}}}\\&{\rm{ }} = \frac{1}{{x\sqrt {1 - {x^2}} }} + \frac{{{x^2} + 4x + 1}}{{{{\left( {x + 2} \right)}^2}}} \end{align}

You are urged to work out the solution on your own.

\begin{align}\text{(d)}\qquad\frac{{d\left( {f\left( x \right)} \right)}}{{dx}}& = \frac{1}{{2\sqrt {4 - {{\tan }^{ - 1}}{x^2}} }} \cdot \frac{{ - 1}}{{1 + {x^4}}} \cdot 2x\\& = \frac{{ - x}}{{\left( {1 + {x^4}} \right)\sqrt {4 - {{\tan }^{ - 1}}{x^2}} }}\end{align}

Example - 28

If f '(x) = g(x), find the derivative of  $${f^{-1}}\left( x \right)$$

Solution: To evaluate the required derivative, we can apply the chain rule on the relation:

\begin{align}& \qquad f\left( {{f^{ - 1}}\left( x \right)} \right) = x\\ &\Rightarrow \frac{d}{{dx}}\left\{ {f\left( {{f^{ - 1}}\left( x \right)} \right)} \right\} = \frac{d}{{dx}}\left( x \right) = 1\\ &\Rightarrow f'\left( {{f^{ - 1}}\left( x \right)} \right)\frac{d}{{dx}}\left( {{f^{ - 1}}\left( x \right)} \right) = 1\\& \Rightarrow \frac{d}{{dx}}\left( {{f^{ - 1}}\left( x \right)} \right)\frac{1}{{f'\left( {{f^{ - 1}}\left( x \right)} \right)}} = \frac{1}{{g\left( {{f^{ - 1}}\left( x \right)} \right)}}\end{align}

For example, we know that \begin{align}\frac{d}{{dx}}\left( {\sin x} \right) = \cos x\end{align}

\begin{align} \Rightarrow \frac{d}{{dx}}\left( {{{\sin }^{ - 1}}x} \right) & = \frac{1}{{\cos \left( {{{\sin }^{ - 1}}\left( x \right)} \right)}}\\& = \frac{1}{{\cos \left( {{{\cos }^{ - 1}}\sqrt {1 - {x^2}} } \right)}}\\ &= \frac{1}{{\sqrt {1 - {x^2}} }}\end{align}

In this way, we can evaluate the derivative of any inverse function, given the derivative of the original function.